A singleplex IgE test to a mixture of molecules from multiple airborne allergen sources: Innovating in vitro screening of respiratory allergies. Issue 11 (1st November 2022) - Potapova, Ekaterina; Panetta, Valentina; Grabenhenrich, Linus; Icke, Katja; Grübl, Armin; Müller, Christoph; Zepp, Fred; Schuster, Antje; Wahn, Ulrich; Lau, Susanne; Keil, Thomas; Matricardi, Paolo Maria
Abstract: Background: In vitro immunoglobulin E (IgE) tests can be better standardized if based on molecules rather than extracts. However, singleplex screening tests for respiratory or food allergies are still based on extracts only. Target: To validate a novel singleplex IgE screening test for respiratory allergies, based on a mix of major allergenic molecules Der p 1, Der p 2, Fel d 1, Can f 1, Can f 2, Can f 3, Can f 5, Bet v 1, Phl p 1, and Art v 1 (Molecular SX01, NOVEOS, HYCOR, USA), and requiring only four microliters (μl) of serum. Methods: We examined six subsets of sera from participants of the German Multicenter Allergy Study (MAS) birth cohort enrolling 1314 newborns during 1990: (1) monosensitized ( n  = 58); (2) polysensitized ( n  = 24); (3) nonsensitized, with total IgE levels above ( n  = 24) or (4) below ( n  = 24) 300 kU/L; (5) sensitized to milk and/or egg but not to airborne allergens ( n  = 24); and (6) sera of children aged ≤5 years at their earliest IgE monosensitization to airborne allergens ( n  = 41). Sera were analyzed with the novel molecular SX01 test (NOVEOS) and with three categories of comparators: ImmunoCAP Phadiatop SX01, extracts, and molecules of D. pteronyssinus, cat, dog, grass, and birch. Sensitivity, specificity, positive and negative predictive values were calculated. Quantitative interrelationships were determined using Spearman's rank‐order correlation coefficient and Bland–Altmann plots. Results: The molecular SX01 test predicted the outcome of IgE tests based on molecules, extracts, or Phadiatop in 188 (96.4%), 171 (87.7%), and 171 (87.7%) of the 195 sera, respectively. Accordingly, sensitivity was 93.5%, 89.0%, and 82.4%, whereas specificity was 100%, 97.6%, and 96.1% when compared with molecular, extract, and Phadiatop tests, respectively. Inconsistent outcomes were largely confined to sera with IgE‐Ab levels around the cutoff value of 0.35 kU/L, except for 5/195 (2.5%) sera, containing high levels of IgE to Phl p 5 and/or Alt a 1 only. IgE levels measured by the molecular SX01 test and with IgE tests to molecules, extracts, and Phadiatop were highly correlated (rho 0.90; p  < .001), (rho 0.87, p  < .001), (rho 0.84, p  < .001), respectively. The novel molecular SX01 test detected IgE‐Ab in 27/28 (sensitivity 96.4%) of the sera of preschool children at their earliest IgE sensitization to the same molecules. Discussion: Our study validates the prototype of a novel category of IgE test, based on molecular mixes. The test's rather good precision and accuracy in early screening IgE sensitization to airborne allergens in German children may be further improved by adding a few other molecules, such as Phl p 5 and Alt a 1.